The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.33915/etd.5408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anticipatory Socialization Stage of Division I Student-Athletes: The Content, Characteristics, and Functions of Memorable Messages

Abstract: The purpose of this dissertation was to explore the socialization of Division I studentathletes prior to their arrival on campus via the framework of organizational socialization and assimilation stage models, and by specifically examining the content, characteristics, and functions of the memorable messages they receive during their anticipatory stage of socialization. Using first cycle, initial coding and second cycle, pattern coding, results indicated that the content of student-athletes' memorable messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 219 publications
(611 reference statements)
0
4
0
Order By: Relevance
“…To date, only a few studies have focused on the memorable messages that athletes receive from coaches, which is problematic, given coaches are the most common sources of athletes’ memorable messages (Cranmer, 2015). The current study recognizes the discursive nature of the athlete–coach relationship by focusing on specific messages that athletes receive from head coaches and also demonstrates that specific topics of interest can be isolated within these messages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few studies have focused on the memorable messages that athletes receive from coaches, which is problematic, given coaches are the most common sources of athletes’ memorable messages (Cranmer, 2015). The current study recognizes the discursive nature of the athlete–coach relationship by focusing on specific messages that athletes receive from head coaches and also demonstrates that specific topics of interest can be isolated within these messages.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the categories identified within this study are consistent with themes of other athlete–coach studies (e.g., importance of success, instruction, relationships). Most notably, the importance of effort within sport has been found within numerous studies that have examined the memorable messages received by youth (Starcher, 2015), high school (Kassing & Pappas, 2007), and collegiate athletes (Cranmer, 2015). Within this study, the importance of effort is illustrated across all three types of supportive messages.…”
Section: Discussionmentioning
confidence: 99%
“…Personal-relational identity gap is experienced when there is a discrepancy between daughters' view of themselves and how they are viewed by In addition to adding to CTI literature and its application, this dissertation expands research on the use of memorable messages in the field of organizational communication and family communication in two ways. First, results of this dissertation prove useful in a comparative sense, in evaluating whether memorable messages on work/family tend to be associated with circumstances (e.g., in the home or in public places) and sources (e.g., mothers or fathers) different from those reported in studies of other communication context (e.g., Cranmer, 2015;Holladay, 200).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Memorable messages have been used as a unit of communication analysis in a plethora of contexts. Examples are gender socialization of new university faculty (e.g., Dallimore, 2003), organizational newcomer socialization (e.g., Barge & Sclueter, 2004;Stohl, 1986), volunteerism with nonprofit organization (e.g., Steimel, 2013), perceptions about aging (e.g., Fung & Carstensen, 2003;Holladay, 2002), constructions of the sense of who one is as an individual (Heisler & Ellis, 2008); college life (e.g., Dunleavy & Yang, 2015;Kranstuber, Carr, & Hosek, 2012;Wang, 2012), nurses' support messages (Ford & Ellis, 1998), illness and healthcare (e.g., Cooke-Jackson, Orbe, Johnson, & Kauffman, 2014;Lauckner et al, 2012;Smith et al, 2010), sports socialization (e.g., Colon, 2011;Cranmer, 2015;Kassing & Pappas, 2007;Starcher, 2015;), end-of-life conversations about religious faith (e.g., Keeley, 2004), and-particularly useful and similar to this study-family and work (Medved, Brogan, McClanahan, Morris, & Shepherd, 2006). found that men and women received similar messages about the role that family should play in their lives; however, women were more frequently encouraged toward selecting work that would allow them to prioritize family needs, and were also advised to exit the workforce after the birth of a child.…”
Section: Memorable Messagesmentioning
confidence: 99%